OP0015 Ultrasound-Defined Tenosynovitis is a Strong Predictor of Early Rheumatoid Arthritis. (9th June 2015) - Sahbudin, I.; Pickup, L.; Cader, Z.; Abishek, A.; Buckley, C.D.; Allen, G.; Nightingale, P.; de Pablo, P.; Raza, K.; Filer, A.
Abstract : Background: The EULAR Study Group for Risk Factors for Rheumatoid Arthritis (RA) recommends identification of new biomarkers for prediction of RA in early undifferentiated disease. The OMERACT Ultrasound Task Force recently established that US is a reproducible tool for evaluating tenosynovitis (TS) in RA 1, which is a common manifestation of early RA. At present, the value of US-defined TS in the prediction of early RA is unknown. Objectives: To explore the ability of US-defined TS to predict early RA compared with clinical and serological variables in an unselected very early arthritis cohort. Methods: 107 patients with clinically apparent synovitis of at least one joint and symptom duration ≤3 months underwent clinical and multiple tendon US assessments and outcome was determined after 18 months by 1987 American College of Rheumatology criteria. A blinded US assessment determined the presence of grey scale and Power Doppler (PD) TS at 16 tendon regions: bilateral fingers (extensor and flexor compartments), wrists (extensor and flexor compartments), shoulders (biceps tendon), ankles (anterior extensors, peroneals, posterior tibialis) using a Siemens Acuson Antares scanner and 5–13 MHz linear array transducer. Grey scale and PD TS definition was based on the OMERACT Ultrasound Task Force recommendations 1 and recorded as binary outcomes. We compared the predictive values of US-defined TS with clinical and serological variables. Results: 43 patients developed RA (VERA), 20 patients developed non-RA persistent disease (NRAP) and 44 patients had resolving disease at follow-up. A total of 1712 tendon regions in 107 patients were included in the analysis. All patient groups had evidence of tenosynovitis in one or more tendon compartments during baseline assessment (VERA 86%, NRAP 75%, resolving 70%). There were significant differences in the distribution of tendon involvement between the three groups including the Extensor Carpi Ulnaris tendon (ECU); [VERA 54%, NRAP 15%, resolving 18%; (p<0.001)]. TS ultrasound variables were superior to clinical variables (early morning stiffness, symmetrical arthritis and hand joint arthritis) in the prediction of early RA. Conclusions: This is the first study to show that US-defined TS is a strong predictor of early RA. Hand and ECU tendon scanning provides the optimal minimal ultrasound data to predict early RA. References: Naredo E, D'Agostino MA, Wakefield RJ, et al. Reliability of a consensus-based ultrasound score for tenosynovitis in rheumatoid arthritis. Ann Rheum Dis 2013;72(8):1328-34. Disclosure of Interest: None declared